Examınatıon of the leadership characteristics of individual and team sports coaches according to some demographic variables - Ateş, Nurdan (2023)
Coaches' leadership orientations play an important role in their professional success. This study aims to examine coaches' leadership orientation behaviors according to certain socio-demographic variables. In the study, it has been used a type of quantitative research using a 'descriptive survey' model. The research is conducted with individual and team coaches (n=196). Among the coaches, 55.6% are individual coaches, while 44.4% are team coaches. The Multidimensional Leadership Orientation Scale and a Demographic Data Form have been used to collect information. For statistical analysis, it is determined whether the assumption of normal distribution of the data is met or not through Kolmogorov-Smirnov and Shapiro-Wilk tests. For examining the status of leadership orientation with respect to the relevant variables, parametric (Independent Samples t-test, One-Way Analysis of Variance ANOVA) hypothesis tests have been applied, taking into account the results of the normality tests. The study has revealed that coaches' leadership orientation scores differ significantly according to age and sports branch variables (p<0.05). As a result of the research, it is determined that coaches aged 21-30 and those in individual sports prefer '’Structural and Political’' behavior. Furthermore, coaches' leadership orientations are found not to be influenced by gender, income status, years of coaching, and educational status.